HOW IMPORTANT IS STRENGTH TRAINING FOR BASKETBALL PLAYERS? - Cabarkapa, Dimitrije (Sport- és Egészségtudományi füzetek, 2025)
It is well known that strength training can induce notable improvements in muscle force and power production, body composition, and motor control, ultimately leading to en-hancement in sports performance. Previous research has revealed a strong relationship between maximal upper- and lower-body strength and playing time on various levels of basketball competition (e.g, youth, collegiate). Also, greater levels of lower-body strength and power were shown to be positively associated with the players’ ability to compete at higher levels of play (e.g., EuroLeague, NBA). Similarly, greater concentric, eccentric, and isometrics strength were found to be strongly correlated with athletes’ performance on change-of-direction tests (e.g., 505 and T-test). Moreover, the findings of a recently published research report indicat-ed that both male and female basketball players needed to possess adequate levels of upper- and lower-body strength to attain satisfactory free-throw, two-point, and three-point shooting efficiency. Thus, it is of critical importance for sports practitioners to focus on developing and implementing ad-equately periodized strength training programs throughout the full competitive season span to help athletes improve on-court basketball performance.